A Mayer optimal control problem on Wasserstein spaces over Riemannian manifolds. Issue 16 (2022) - Jean, F.; Jerhaoui, O.; Zidani, H.
Abstract: This paper concerns an optimal control problem on the space of probability measures over a compact Riemannian manifold. The motivation behind it is to model certain situations where the central planner of a deterministic controlled system has only a probabilistic knowledge of the initial condition. The lack of information here is very specific. In particular, we show that the value function verifies a dynamic programming principle and we prove that it is the unique viscosity solution to a suitable Hamilton Jacobi Bellman equation. The notion of viscosity is defined using test functions that are directionally differentiable in the space of probability measures.